PENGARUH KEPRIBADIAN, LINGKUNGAN KELUARGA, DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA MANAJEMEN UNIVERSITAS KADIRI - Astutik, Marina Dwi; Sustiyatik, Enni; Rukmini , Meme (Universitas Nusantara PGRI Kediri, 2023)
This research aims to evaluate the impact of Personality, Family Environment, and Entrepreneurship Education on Entrepreneurial Interest in Management Students at Kadiri University. The research approach was quantitative with 92 respondents from a total population of 1,241 selected randomly. The results of multiple linear regression analysis show that Personality (X1) has a positive and significant effect on Entrepreneurial Interest, with a calculated T value of 5.945 and a significance of 0.000. Likewise, Family Environment (X2) also has a positive and significant effect on Interest in Entrepreneurship, with a calculated T value of 4.262 and a significance of 0.000. However, Entrepreneurship Education (X3) does not have a significant influence, with a calculated T value of 1.350 and a significance of 0.180. Simultaneously, these three factors have a positive and significant influence on the Entrepreneurial Interest of Kadiri University Management.